2011
DOI: 10.1103/physrevb.84.085207
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties and investigations of low thermal conductivity in Ga-doped Cu2GeSe3

Abstract: In this study, we have synthesized a series of low thermal conductivity diamond-like materials with the general formula Cu 2 Ga x Ge 1-x Se 3 for 0 ≤ x ≤ 0.1, and their transport properties were evaluated to establish their suitability for TE based waste heat recovery applications. We report results for the Seebeck coefficient (S), electrical resistivity (ρ), thermal conductivity (κ), Hall coefficient (R H ), crystal structure, and elastic properties of Cu 2 Ga x Ge 1-x Se 3 for x = 0.01, 0.03, 0.05, 0.07 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 29 publications
6
57
3
Order By: Relevance
“…22 The ZT value of Bi 0.925 Ca 0.075 CuSeO at 873 K is also higher than that of 0.7 for Bi 0.90 Sr 0.10 CuSeO at 873 K. 21 The present ZT of 0.9 is higher than most thermoelectric materials with intrinsically low thermal conductivity reported so far. [13][14][15][16][17][18][19][20] Therefore, it can be concluded that the higher thermoelectric performance of BiCuSeO is mainly due to the intrinsically low thermal conductivity of the material.…”
Section: Structural and Thermoelectric Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…22 The ZT value of Bi 0.925 Ca 0.075 CuSeO at 873 K is also higher than that of 0.7 for Bi 0.90 Sr 0.10 CuSeO at 873 K. 21 The present ZT of 0.9 is higher than most thermoelectric materials with intrinsically low thermal conductivity reported so far. [13][14][15][16][17][18][19][20] Therefore, it can be concluded that the higher thermoelectric performance of BiCuSeO is mainly due to the intrinsically low thermal conductivity of the material.…”
Section: Structural and Thermoelectric Propertiesmentioning
confidence: 99%
“…44 Indeed, BiCuSeO exhibits a lower sound velocity, 23 Young's modulus and lattice thermal conductivity at 300 K than other oxides, 40 In addition to the analysis of Young's modulus (E), which is related to the chemical bonding strength, the Gruneisen parameter (g) is also relevant in evaluating the intrinsically low thermal conductivity. 11,18 The Gruneisen parameter (g) is often referred to as a temperaturedependent anharmonicity parameter that reflects how much phonon vibrations in a crystal lattice deviate from harmonic oscillations. Anharmonicity of the chemical bond drives the phonon-phonon umklapp and normal processes that limit the lattice thermal conductivity.…”
Section: Origin Of the Low Thermal Conductivitymentioning
confidence: 99%
See 3 more Smart Citations